Management of oil and natural gas by PT. pertamina in the context of national energy security - Syawal Fahmi; Mohammad Aldilla Muntazar; Rita Paramawati; Asadur Rahman Muhammad (Indonesian Institute For Counseling, Education and Therapy, 2026)
This study examines the role of PT. Pertamina in managing oil, natural gas, and renewable energy in Indonesia, particularly in the context of national energy security. Using a qualitative approach with a literature review and library research, the study evaluates Pertamina's contribution to Indonesia's energy supply through its oil and gas production, refining capacity, and investments in renewable energy. The findings indicate that Pertamina plays a crucial role, contributing 50% of the nation’s crude oil production and 30% of natural gas output. In addition to its significant contribution to upstream production, the company expanded its refining capacity from 1.0 million barrels per day (bpd) in 2018 to 1.5 million bpd in 2023, strengthening domestic fuel processing capabilities and reducing dependence on imported refined petroleum products. Additionally, the company has significantly invested in geothermal energy as part of its renewable energy development strategy. Despite these advancements, the study identifies several challenges, including regulatory barriers, global oil price volatility, and the financial and technical obstacles to transitioning to renewable energy. The paper concludes that while Pertamina has made substantial progress in enhancing Indonesia's energy security, addressing these challenges is essential for achieving long-term sustainability. The study recommends further research into the regulatory and technological aspects of energy transition, as well as the socio-economic impacts of biofuel production.